Effects of electric current on growth, chlorophyll a content, pulse amplitude modulation response, and new chamber formation of the foraminifera Amphistegina lobifera - Federica Rebecchi; Davide Lattanzi; Sigal Abramovich; Patrizia Ambrogini; Fabrizio Frontalini; Christiane Schmidt (PANGAEA, 2025)
The electrodeposition of calcium carbonate via low-level electric current has been shown to enhance growth in calcifying organisms, providing a valuable tool for restoration programs. This dataset documents experiments to investigate the effects of low electric current densities on the larger benthic foraminiferal species Amphistegina lobifera. Samples of living foraminifera were collected at Haifa, Shikmona Station, Mediterranean Sea, Israel. The datasets represent two experiments conducted one after the other from April to May 2023, testing the same range of low level electric currents on A. lobifera and measuring different paraments. The first experiment evaluated the effects of electric current on the physiology of its endosymbionts using PAM fluorometry and chlorophyll a content analysis. The second experiment assessed the growth rate through morphological analysis and calcein labeling while also tracking the physiology of the endosymbionts using PAM fluorometry. Positive growth rate and newly formed chambers were recorded at a current density of 1 μA/cm^2 and 1.43 μA/cm^2. Further studies could focus on using this current density and manipulating other parameters to enhance growth through a multi-pathway approach. These results provide insights into physiological effects of electric current densities on the benthic foraminifera A. lobifera.